db/db Mice Exhibit Features of Human Type 2 Diabetes That Are Not Present in Weight-Matched C57BL/6J Mice Fed a Western Diet - Susan J. Burke; Heidi M. Batdorf; David H. Burk; Robert C. Noland; Adrianna E. Eder; Matthew S. Boulos; Michael D. Karlstad; J. Jason Collier (Journal of Diabetes Research)
To understand features of human obesity and type 2 diabetes mellitus (T2D) that can be recapitulated in the mouse, we compared C57BL/6J mice fed a Western-style diet (WD) to weight-matched genetically obese leptin receptor-deficient mice (db/db). All mice were monitored for changes in body composition, glycemia, and total body mass. To objectively compare diet-induced and genetic models of obesity, tissue analyses were conducted using mice with similar body mass. We found that adipose tissue inflammation was present in both models of obesity. In addition, distinct alterations in metabolic flexibility were evident between WD-fed mice and db/db mice. Circulating insulin levels are elevated in each model of obesity, while glucagon was increased only in the db/db mice. Although both WD-fed and db/db mice exhibited adaptive increases in islet size, the db/db mice also displayed augmented islet expression of the dedifferentiation marker Aldh1a3 and reduced nuclear presence of the transcription factor Nkx6.1. Based on the collective results put forth herein, we conclude that db/db mice capture key features of human T2D that do not occur in WD-fed C57BL/6J mice of comparable body mass.